Pinteresque Dialogue - Uchman, Jadwiga (Text Matters: A Journal of Literature, Theory and Culture, 2017)
The expression “Pinteresque” describing the characteristic features of Harold Pinter’s artistic output, established its position as a literary critical denominator many years ago. The aim of this article is to analyze some of the specific aspects of the playwright’s use of language. On several occasions, the artist made comments pertaining to certain issues concerning communication. He rejected the idea of the alienation of language and promoted the concept of evasive communication, thus showing people’s unwillingness to communicate. He also spoke about two kinds of silence, the first referring to a situation where there is actual silence, when “no word is spoken,” and the second , when “a torrent of language is being employed” in order to cover the character’s “nakedness.” Accordingly, Pinter’s plays may, depending on their perspective, be treated as dramas of language or of silence. This led Peter Hall, Pinter’s favourite theatre director and also a close friend, to notice that in the playwright’s oeuvre there is a clear distinction beween three dots, a pause and a silence. This article discusses in detail the uneven distribution of pauses and silences in Harold Pinter’s 1977 play, Betrayal. It becomes evident that the use of different kinds of silence clearly indicates the emotional state of the characters at any given moment.